Upfront Combination Therapy for Type 2 Diabetes Mellitus Using Triple Oral-glucose Lowering Drugs: a Case-based Review - Syed Ibrahim Jamallulail (Asian Journal of Medicine & Health Sciences, 2022)
Type 2 Diabetes mellitus (DM) is a complex metabolic condition characterized by persistent hyperglycaemia and other metabolic abnormalities. Untreated, this condition leads to significant morbidity and mortality. The therapeutic aim in this condition is to establish early normoglycaemia to prevent permanent pancreatic beta islet dysfunction and development of irreversible vascular damage. American and Malaysian guidelines recommend upfront initiation of insulin therapy for patients with catabolic symptoms and very severe hyperglycaemia. Unfortunately, the acceptance rate for insulin therapy among newly diagnosed type 2 DM patients is low. We report the case of a 71-year-old lady with newly diagnosed type 2 DM. Her random and fasting glucose were 17.3 mmol/L and 13.3 mmol/L respectively which did not improve with diet control. She was commenced on a combination of metformin, sitagliptin and empaglifozin. Her fasting and two-hour post-prandial glucose was 7.5mmol/L and 8.3 mmol/L respectively, after 2 weeks of this combination of oral glucose lowering drugs. We review the basic physiology and pharmacological rationale for the combination utilised and other potential non-insulin regimes. Initiation of oral glucose lowering drug combination is effective in achieving early glycaemic optimisation in patients with very severe hyperglycaemia in the absence of catabolic symptoms and ketosis. The combination we utilised have minimal risk of hypoglycaemia and is ideal for initiation in the out-patient setting.